Warehouse Inventory Management System for the Smooth Delivery of Cargo to Reduce Dwelling Time at the Port of Tanjung Emas Semarang - Elwas Cahya Wahyu Pribadi; Raja Oloan Saut Gurning; Eko Susanto (Institut Teknologi Sepuluh Nopember, 2020)
Delivery cargo is a job of moving goods from the pile or a heap in the warehouse, handing it to be arranged on the vehicle and sending it to the receiving warehouse (consignee). The delivery of goods in the form of fertilizer carried out by PT. PUSRI (Pupuk Sriwijaya) at the Port of Tanjung Emas Semarang from the first line warehouse to each branch of the receiving warehouse throughout Indonesia experienced problems. The problem faced in the activities of the cargo delivery is the delay in the process of shipping goods caused by one of them by a bad warehouse inventory management system so that dwelling time is getting longer. Therefore, a good warehouse inventory management system is needed. This system has several functions, among others, as storing detailed information of goods and pointing to the location of goods. Warehouse inventory management system created with the Internet of Things was developed to track the goods / products that were previously recorded. In monitoring all information used Aduino. the web was built to provide comfort and ease in finding goods / products. With this system the cost required is low and efficient and very easy to use.